Variation in Response to Pharmacological Intervention with Risperidone and the Role of Adjuvant Medications in the Treatment of Autism Spectrum Disorders: A Systematic Review and Meta-analysis - Sharanabasayyaswamy Hiremath; Srinivas L. Devendrappa (Universitas Padjadjaran, Indonesia, 2022)
Non-genetic traits as predictors of variation in response to pharmacological interventions in ASD need to be identified for better management. This review aims to identify these non-genetic traits and the role of adjuvant medications in ASD. Electronic database searches in PUBMED and Cochrane libraries were conducted using MeSH search terms